THE MARGINAL AND INTERNAL FIT OF COCR ALLOY SINGLE CROWNS WITH PREPARATION DESIGNS INCLUDING AUXILIARY FEATURES; CAD/CAM VERSUS CONVENTIONAL TECHNIQUE - K. Walczak; D. Friedrichs; H. Meissner; K. Boening (Czech Dental Chamber, 2020)
Objectives: Evaluation of the influence of complex tooth preparation designs with incorporated auxiliary features on the marginal and internal fit of computer-aided design (CAD), and either additive (SLM) or subtractive (milling) computer-aided manufactured (CAM) and conventionally cast CoCr alloy single crowns (SC). Material and methods: Artificial teeth were prepared with four different preparation designs: chamfer standard preparation (SP, as control), chamfer preparation with occlusal isthmus (OP), chamfer preparation with proximal boxes (BP) and chamfer preparation with buccal/lingual grooves (GP). Five crowns were made from each preparation design by cast technique (CT), milling technique (MT) and selective laser melting (SLM). The marginal and internal fit of the crowns was analysed by the silicone replica technique. The internal fit was evaluated by measuring axial, occlusal and gaps within auxiliary features. Mean and maximal gap widths values were evaluated. The Kruskal-Wallis test and U-test (Bonferroni adjusted) were used for the statistical analysis (p ≤ 0.05). Results: For SP and OP, the marginal fit was similar between CT and MT as well as between CT and SLM. For SP and OP, the occlusal gaps were the lowest for CT and significantly different to SLM. For BP and GP, the marginal fit was statistically significantly better for CT than MT. The internal fit for BP and GP was best for CT. Conclusions: Within all preparation designs with auxiliary features, only the CT achieved clinically acceptable values for both marginal and internal fit. Tested CAD/CAM systems and their software versions need further improvement to implement preparation designs with auxiliary features.